MENINGKATKAN KAPASITAS SUMBER DAYA MANUSIA DESTINASI PARIWISATA TERINTEGRASI DI KABUPATEN KUDUS - Donna Ekawaty; Ruth Olivera Kayko (Bajang Institute, 2023)
The density of visits to tourist destinations by tourists, both local tourists, domestic tourists, and foreign tourists, shows that tourism has moved faster than predicted by the Governments. Facing this, the Governments took the initiative to increase the capacity of human resources (HR) for each tourist destination in Indonesia. In reality, not all human resources (HR) are fulfilled and adequate. This condition attracts researchers to examine the development of tourism destinations through increasing integrated human resource capacity in Kudus Regency. The research was conducted to develop tourism destinations through integrated human resource capacity building. The research used interpretive ethnographic methods and collaborative action research methods chosen as a measure of the success of suitability of the abilities possessed by human resources in tourism destinations by conducting direct interviews with training participants, understanding tests, site surveys, and facility analysis. Then take action based on the training by conducting a competency test from a Professional Certification Institution (LSP). The results show that human resources (HR) in tourism destinations in Kudus Regency are partially integrated. It can be from their knowledge, skills, and attitudes towards tourists. So far, human resource capacity building has been limited to training and outreach, so it has not fully integrated. The renewal in this research is in the form of training with the output of a competency test of cooperation between the government and Professional Certification Institution (LSP) by utilizing the facilitation of the Ministry of Tourism of the World Bank program capable of producing complete integration.